O jogo Probio e a visão sistêmica em educação ambiental - Mendes, Michel (My University, 2017)
The objective of this research is to investigate the educational character of Probio game against systemic view in environmental education in order to situate its relevance to the construction of a new look on the man-nature relationship. The Probio is an educational board game and cooperative character, prepared by the Ministry of Environment, Ministry of Education and the University of Brasilia, released in 2006. The scientific and social relevance of the dissertation is justified by the insertion in the context of High School, a level still little explored in master's and doctoral research. The theoretical framework is based in the contributions, mostly of the authors Capra (2000, 2001) and Capra and Luisi (2014) on the systemic view; Carvalho (2011), Dias (2004), Reigota (2010) and Sauvé (2005a, 2005b), concerning environmental education; Saito (2006), regarding the Probio game; Brotto (1999, 2001, 2003) and Orlick (1989) on cooperative game; and Brougère (1998a) and Huizinga (2000) in relation the game and the education. The empirical application of the research was carried out in the State College Immigrant, located in the city of Caxias do Sul, with eight first-year students of the Polytechnic School, between the months of April and May 2016. The participation of students was through volunteering and attending the number of participants allowed the game. The research is qualitative and exploratory, with procedures that characterize the action research, taking advantage of the following resources for the construction of data: questionnaire, field diary and focus group; and the use of audio recorder and camera. The data analysis is based on the Text Analysis Discourse, in Moraes and Galiazzi (2011). The results evidenced that the game Probio can guide the formation of a vision of interdependence, although, according to the evidences presented, this change of vision has appeared in a still preliminary and partial way. The main contributions of the game to the systemic view are located in the portfolios and the cards conflict and action, in which multifaceted contexts indicate the complexity of relationships built by man with nature.
O objetivo desta pesquisa é investigar o caráter educacional do jogo Probio frente à visão sistêmica em educação ambiental, a fim de situar sua relevância para a construção de um novo olhar sobre a relação homem-natureza. O Probio é um jogo educativo de tabuleiro e de caráter cooperativo, elaborado pelo Ministério do Meio Ambiente, Ministério da Educação e Universidade de Brasília, lançado em 2006. A relevância científica e social da dissertação justifica-se pela inserção no contexto do Ensino Médio, nível ainda pouco explorado em pesquisas de mestrado e doutorado. O aporte teórico está pautado nas contribuições, em sua maioria, dos autores Capra (2000, 2001) e Capra e Luisi (2014), sobre a visão sistêmica; Carvalho (2011), Dias (2004), Reigota (2010) e Sauvé (2005a, 2005b), a respeito de educação ambiental; Saito (2006), no que tange o jogo Probio; Brotto (1999, 2001, 2003) e Orlick (1989), sobre jogo cooperativo; e Brougère (1998a) e Huizinga (2000) em relação ao jogo e à educação. A aplicação empírica da pesquisa foi realizada no Colégio Estadual Imigrante, localizado no município de Caxias do Sul, com oito estudantes do primeiro ano do Ensino Médio Politécnico, entre os meses de abril e maio de 2016. A investigação é de caráter qualitativo e exploratório, com procedimentos que caracterizam a pesquisa-ação, valendo-se dos seguintes recursos para a construção dos dados: questionário, diário de campo e grupo focal; além do uso de gravador de áudio e câmera fotográfica. A análise dos dados toma como base a Análise Textual Discursiva, de Moraes e Galiazzi (2011). Os resultados evidenciam que o jogo Probio pode orientar a formação de uma visão de interdependência, embora, de acordo com as evidências apresentadas, essa mudança de visão tenha se apresentado de modo ainda preliminar e parcial. As principais contribuições do jogo para a visão sistêmica situam-se nos portfólios e nas cartas conflito e ação, em que contextos multifacetados sinalizam a complexidade das relações construídas pelo homem com a natureza.
Keywords: Projeto de Conservação e Utilização Sustentável da Diversidade Biológica Brasileira; Educação ambiental - Estudo e ensino (Ensino médio); Jogos educativos; Environmental education; Systemic view; Probio game; High school; Action research